2021
DOI: 10.1177/10760296211047231
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Thromboelastography (TEG) for the Diagnosis of Death in Infected Patients

Abstract: In this study, we want to investigate the clinical value of each index of thromboelastography (TEG) on the prognosis of infected patients. The clinical baseline data and TEG test results of 431 infected patients in our hospital’s emergency department between January 2018 and December 2018 were selected. And the patients were divided into death and survival groups to analyze the predictive value of each index of TEG and the joint model on the death of infected patients. In the correlation study of C-reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…TEG parameters can vary based on the sampling time. 21 22 Thus, analysis of follow-up TEG data could have strengthened our results. Finally, this was a single-center study.…”
Section: Discussionsupporting
confidence: 59%
“…TEG parameters can vary based on the sampling time. 21 22 Thus, analysis of follow-up TEG data could have strengthened our results. Finally, this was a single-center study.…”
Section: Discussionsupporting
confidence: 59%
“…To our knowledge, this is the first assessment of whether thromboelastographic parameters can be used to identify patients with severe COVID-19 who are more likely to die within 30 days after ICU admission. Our results suggest that TMA may be useful as a prognostic indicator, which may reflect its ability to assess interaction between coagulation factors and platelets ( 24 ). Indeed, we found that TMA correlated with prothrombin time, international normalized ratio, and D-Dimer.…”
Section: Discussionmentioning
confidence: 83%
“…Some studies stated that TEG parameters were specific but not sensitive in predicting hypercoagulability and its sensitivity and specificity may vary significantly in different populations (4,8). Among all parameters, K time was the most sensitive parameter (48.96%) and time to MA (TMA) and α-angle were the most specific parameters (94.55% and 87.27%, respectively) in predicting hypercoagulability in COVID-19 patients (6).…”
Section: Resultsmentioning
confidence: 99%
“…TEG results are presented in almost 20 different parameters, including reaction time (R), kinetic time (K), α-Angle, maximum amplitude (MA), and clot lysis at 30 minutes after maximum clot strength (Ly30). TEG could describe all conventional coagulation tests in one graph, making this test superior and more effective in assessing the presence of coagulopathy (6)(7)(8). Therefore, this study aimed to assess the association of selected TEG parameters and TEG results with the survival status of COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%